Gender and age variations in neuropsychiatric adverse events of cetirizine and levocetirizine: a disproportionality analysis of ICSRs from FAERS and EudraVigilance data - Yang, Tingting; Wu, Xiaoxiao; Yi, Xueliang; Xiang, Chunlin; Yang, Yinping; Yang, Chen; Zheng, Xiaoxia; Han, Yuhong; Wang, Yiping (Frontiers in Pharmacology, 2026)
BackgroundThis study analyzed neuropsychiatric adverse drug events (ADEs) associated with cetirizine and levocetirizine using data from the FDA Adverse Event Reporting System (FAERS) and EudraVigilance databases to inform safer clinical use for different age and gender groups.MethodsWe performed disproportionality analyses (ROR, PRR, BCPNN, MGPS) using data from the FAERS (Q1 2004 to Q3 2025) and the EudraVigilance database (January 2002 to December 2025). In addition, stratified analysis was conducted for the top 20 reported ADEs across different sex and age groups.ResultsSomnolence, dizziness, headache, and insomnia are common adverse drug reactions (ADRs) with high disproportionality signals for both cetirizine and levocetirizine. Cetirizine was generally associated with higher signal intensities for depression, anxiety, and drug abuse/dependence compared to levocetirizine, with unique reports of cognitive impairment and migraine. In contrast, levocetirizine showed stronger signals not only for sleep-related ADRs but also for serious psychiatric events, including suicide attempts and suicidal ideation. Among levocetirizine users, febrile convulsions were more frequently reported in males. Additionally, pediatric patients exposed to levocetirizine were reported to have febrile convulsion and epilepsy. In the elderly, reports associated with cetirizine included subarachnoid hemorrhage, transient ischemic attack, and carotid artery occlusion, while those for levocetirizine included hepatic encephalopathy.ConclusionThese findings highlight the distinct neuropsychiatric risk profiles associated with cetirizine and levocetirizine. This underscores the importance of age- and sex-informed drug selection to optimize their safe use.